Evaluasi Pelaksanaan Program Usaha Peningkatan Pendapatan Keluarga Akseptor Di Kampung Keluarga Berkualitas Tanjung Rawo Dan Layang-Layang Kota Palembang - Sibarani, Yetti Erika; Mudasir, Mudasir; Sakir, Icuk Muhammad (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
Increasing family economic business through the UPPKA group is one part of the poverty alleviation efforts that have been launched by the government targeting poor family groups. The research locus took place in Tanjung Rawo and Layang-Layang KB Village with the aim of research to evaluate the implementation of the UPPKA program in Tanjung Rawo KB Village, Bukit Lama District, Ilir Barat I District and UPPKA in KB Layang-Layang Village, 29 Ilir District, Ilir Barat II District, Palembang City . This research is included in the type of evaluation research using the CIPP evaluation model (Context, Input, Process, and Product). The data in this study were sourced from information obtained directly from informants, documents, books and archives. Data collection techniques used are observation, interviews and documentation. The selection of informants was selected purposively, in this case the informants were selected because they were considered to know the most and were directly related to UPPKA implementation in the field. There were five informants. Data were analyzed by interactive model analysis using the main components: data reduction, data presentation, and drawing conclusions. From the results of the research seen from the context, input, process, and product as a whole the UPPKA program can be carried out although in other indicators there are still not optimal both in terms of human resources and budget, how to carry out activities from socialization, coordination and implementation of roles and support stakeholders.